Mongolia : First Review Under the Stand-By Arrangement; Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Mongolia. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
This paper discusses key findings of the First Review Under the Stand-By Arrangement for Mongolia. The paper reveals that economic activity in Mongolia is slowing and inflation is falling, broadly in line with what was anticipated at the time the program was approved. The authorities' strong policy implementation is working to stabilize the economy. The biweekly foreign exchange auctions are also working well, and the authorities remain committed to allowing exchange rate flexibility in line with market conditions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet